Plasmonic Bi NP-accelerated interfacial charge transfer for enhanced solar-driven ciprofloxacin mineralization. Issue 1 (17th December 2021) - Yue, Cailiang; Zhu, Changqing; Zheng, Wenting; Qiu, Jinli; Du, Zhiling; Ling, Chen; Liu, Fu-Qiang
Abstract : Photocatalytic degradation process of TC by BMO/Bi/BOB- x . Abstract : Highly efficient mineralization of refractory organic pollutants is an admittedly difficult problem for most photocatalytic processes. Herein, a hierarchical type-II heterojunction Bi2 MoO6 /Bi/BiOBr- x (BMO/Bi/BOB- x ) was successfully fabricated via a one-pot solvothermal method. The optimal BMO/Bi/BOB-2 exhibited an ∼80% mineralization ratio of ciprofloxacin under simulated solar irradiation, outperforming most reported photocatalysts. ˙OH was demonstrated to be the dominant reactive species. The ˙OH production capacity of BMO/Bi/BOB-2 increased by 76.2% compared with that of BMO/BOB, highlighting the key role of Bi nanoparticles (Bi NPs). Bi NPs not only induced a strong localized surface plasmon resonance effect to enhance the utilization of visible light, but also acted as an electron mediator to accelerate the separation of e − /h + pairs. Due to the specific redox potential, the separated h + and e − could activate H2 O and O2 to produce ˙OH synchronously. Overall, this work provided a valuable strategy to design a plasmonic Bi NP-enhanced type-II heterojunction for the efficient treatment of refractory organic wastewater.